Anatomy of a Style Analyzer - Stratton, Charles R. (Journal of Technical Writing and Communication, 1989)
Computer programs for analyzing writing style have grown in number and sophistication over the past decade, and the coming decade will see more and more of them. In order to know the capabilities and limitations of such programs and to decide if any of them are right for you, it is important to understand how they work. In this article, the author draws on his background in computational linguistics to explain how computerized style analyzers accomplish the things that they do.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjE5MC8wNHZtLTZlazMtbTZ4Yi0zNW41